Pengaruh Hambatan Samping Akibat Aktivitas Pasar Bandarbuat Terhadap Kecepatan Arus Lalu Lintas - Fathinatul Atika; Purnawan Purnawan (Jurnal Ilmiah Rekayasa Sipil, 2022)
The highway is a mode of land transportation that plays a critical role in linking communities. With an increase in the number of people and the number of activities carried out by the local community, a variety of issues occur, causing traffic delays, notably in front of the Bandarbuat market in Padang City. On hall days (Tuesday and Saturday), the crowded Bandarbuat market causes traffic congestion in front of the market. The goal of this study is to evaluate the features of side barriers found in the market region and to assess their impact on vehicle speed. Taking traffic activities using Drones and Handycams allows for the calculation of traffic volume data, side barriers, and speed. Data processing techniques were used to compare barrier-free areas with those with obstacles to estimate the influence of side barriers on speed. According to the study's findings, the most frequent occurrence of side obstacles was 46 percent of all the segments studied is in the Front of the Market Area (Segment III), resulting in a 20 percent decrease in traffic flow speed from segment I to segment II and a 3 percent decrease in traffic flow speed from segment II to segment III. Meanwhile, the speed climbed by 12% from segment III to segment IV. Parking/Stop Vehicle is the side obstacle variable with the greatest influence or correlation on average speed. The average speed is moderately correlated with variables of side drag of Vehicles Exit/Entrance and Vehicles Against the Current. Pedestrians, on the other hand, have the smallest impact on the average speed.